2010
DOI: 10.3329/jhpn.v28i5.6158
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based Perinatal Outcomes and Complications in Teenage Pregnancy in India

Abstract: Teenage pregnancy is a worldwide problem bearing serious social and medical implications relating to maternal and child health. A cross-sectional observational study was undertaken to compare the different sociodemographic characteristics and perinatal outcomes of teenage primigravida mothers with those of adult primigravida mothers in a tertiary-care hospital in eastern India. A sample of 350 each in cases and comparison group comprised the study subjects. Data were collected through interviews and by observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
137
10
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(199 citation statements)
references
References 15 publications
41
137
10
11
Order By: Relevance
“…This maybe reflects behavioral and cultural diversity among pregnant adolescents across countries [27,28]. Higher proportions (LBW 38.9%, PTB 27.7%) were found in India [29]. We link this to the greater proportion (11%) of young teenagers (15-17 years) in this study, given that inverse relationship between maternal age and adverse fetal outcome [4,30,31].…”
Section: Discussionmentioning
confidence: 82%
“…This maybe reflects behavioral and cultural diversity among pregnant adolescents across countries [27,28]. Higher proportions (LBW 38.9%, PTB 27.7%) were found in India [29]. We link this to the greater proportion (11%) of young teenagers (15-17 years) in this study, given that inverse relationship between maternal age and adverse fetal outcome [4,30,31].…”
Section: Discussionmentioning
confidence: 82%
“…The higher rate of stillbirths among older women may be due to increased risk of congenital anomalies associated with advanced maternal age. In contrast, hospital-based studies conducted in India [28] and Nigeria [29] reported an increased risk of stillbirths in mothers aged less than 20 years. This finding may reflect a lack of education, limited autonomy to make household decisions and poor health-seeking behaviours among teenage women, as reported in Nigeria [30] and India [31].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, hospital-based studies conducted in India [28] and Nigeria [29] reported an increased risk of stillbirths in mothers aged less than 20 years. This finding may reflect a lack of education, limited autonomy to make household decisions and poor health-seeking behaviours among teenage women, as reported in Nigeria [30] and India [31]. Nevertheless, a population-based study from Taiwan reported an increased risk of stillbirths in both older (>40 years) and younger mothers (<20 years) [32].…”
Section: Discussionmentioning
confidence: 97%
“…60.0% mothers had their 1 st pregnancy before 20 years of age. This may result in low birth weights, still births and other peri natal complications [5,6]. Level of education of mothers, their husbands and socio economic background play a major role in attending clinics and receiving proper ante natal checkups.…”
Section: Discussionmentioning
confidence: 99%